Joondalup Invitation Art Prize 2022 - Slatter, Nicole; Slatter, Bruce (2022)
Suburban Sojourn is about attuning to and experiencing the surrounding local environment. It combines image and form, reflecting the way an understanding of place is built up from fragments of spatial and visual information. An understanding of this space develops and is assembled over time as suburbia changes, as the familiar is replaced, and memory mixes with new. The many parts that make up suburban place coexist, as private space adjoins shared public space and boundaries divide the landscape. Differences in architecture represent personal taste and record eras of building style. Nature contributes to this fragmentation with cultivated gardens contrasting untamed verges and native plants competing with the exotic. Suburban Sojourn is part of a larger series of formpaintings that explore the multimodal experience of the suburban built-environment through movement, seeing and feeling in realist representation. The varied scales and forms hope to tune into the space of the suburbs by pushing and pulling the viewer’s attention into the varied surface.